Inverse association between microRNA-124a and ABCC4 in HepG2 cells treated with antiretroviral drugs. (1st September 2016) - Nagiah, Savania; Phulukdaree, Alisa; Chuturgoon, Anil
Abstract: The ATP-binding cassette (ABC) super-family of drug transporters regulates efflux of xenobiotic compounds. The subfamily, multi-drug resistance proteins (MRPs) transports cyclic nucleotides and xenobiotics. Epigenetic modulation of drug transporters is scarcely described. The regulatory role of microRNA (miR)-124a on drug transporter gene ABCC4 was only recently reported. Our study investigated the differential regulation of miR-124a by nucleoside reverse transcriptase inhibitors (NRTIs): Zidovudine (AZT), Stavudine (d4T) and Tenofovir (TFV); at 24 h and 120 h treatments in HepG2 cells. ABCC4 mRNA (qPCR) and ABCC4 protein (western blot) were quantified. Cytotoxicity was evaluated by lactate dehydrogenase (LDH) levels. All NRTIs elevated miR-124a levels at 24 h, with a concomitant decline in ABCC4 mRNA levels ( p <0.05). At 120 h, d4T and TFV elevated miR-124a and depleted ABCC4 mRNA levels ( p <0.0001), while the inverse was observed with AZT ( p <0.005). ABCC4 protein was increased by d4T and TFV at 24h. A significant reduction in protein levels was observed at 120 h in all three treatments ( p <0.005). The disjoint in mRNA and protein levels is likely due to ABCC4 being a membrane bound protein. Following prolonged exposure, membrane integrity was compromised as evidenced by increased LDH leakage ( p <0.005). We conclude antiretroviral drugs have varying effects on miR-124a and ABCC4.